Youth Leadership Development through the Patriot Desa Program of West Java - Azmi, Asraar Kamal; Ikhwan, Hakimul; Listyaningsih, Umi (Populasi, 2024)
The national Youth Development Index (YDI) is still fluctuating. One of the provinces with a lower percentage change in YDI than expected is West Java, which is at the bottom of the list. This is ironic considering that 20% of Indonesia's total youth reside in West Java. In fact, during period 2018-2023, many programs were launched which focused on youth development, such as Patriot Desa. The presence of the Patriot Desa Program did not make the value of Youth Participation and Leadership increase. Therefore, this research aims to find out how the Patriot Desa Program impacts youth leadership development in West Java. The methodology used in this research is qualitative with a case study approach. The research was conducted in Sukaharja and Sukamakmur Village, Sukamakmur Sub-district, Bogor Regency. Data collection techniques through interviews the representatives of the West Java DPMD, Patriot Desa, village secretaries, youth organizations, and local champions. The program followed by young people who became Patriot Desas was able to have an impact on the development of individual and social leadership. In particular, the village patriots who served in the research locations were highly dedicated with a self-sacrificing attitude and always collaborated with various parties, so that they were able to bring about changes in the village in social, economic and environmental aspects. However, these things are also inseparable from the influence of pre-deployment orientation and the role of the regional coordinator who is very supportive as a mentor. Youth involvement in community empowerment programs can be a means of developing youth leadership. Therefore, the government needs to involve more youth in other programs so that there is an increase in the domain value of youth participation and leadership.